P29_059 - 59. Using Eq. 29-2 and Eq. 3-30, we obtain F = q...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
59. Using Eq. 29-2 and Eq. 3-30, we obtain ~ F = q ( v x B y v y B x ) ˆ k= q ( v x (3 B x ) v y B x ) ˆ k whereweusethefactthat B y =3 B x . S incetheforce(attheinstan tcons idered)is F z ˆ kwhere F z = 6 . 4 × 10 19 N, then we are led to the condition q
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 11/12/2011 for the course PHYS 2001 taught by Professor Sprunger during the Fall '08 term at LSU.

Ask a homework question - tutors are online